Jumlah Trombosit pada Pasien Demam Berdarah - Niken Meiriyani (Jaringan Laboratorium Medis, 2020)
Dengue hemorrhagic fever (DHF) is an acute infectious disease caused by the dengue virus. This virus is transmitted by mosquitoes from the genus Aedes, for example Aedes aegypti and Aedes albopictus. Patients who are infected will have symptoms in the form of a mild to high fever, accompanied by headaches, pain in the eyes, muscles and joints, and spontaneous bleeding. DHF in Indonesia, has become a public health problem for the last 45 years since 1968. These cases are spread across 33 provinces and in 436 districts / cities out of 497 districts / cities (88%) in Indonesia. The number of people with Dengue Hemorrhagic Fever (DHF) tends to increase. The laboratory chooses to use a blood cell counter or a hematology analyzer to count the patient's blood cell count. The results of laboratory examinations with platelet counts in dengue fever patients were obtained 19 (14.84%) samples of patients with platelets d below 100,000 per micrometer (mcL) from 128 patients from January to March 2019. With 2 days of fever patients were 44 people. , 37 patients had fever for 4 days, and 5 fever patients were 47, in normal numbers and brought to a normal range of 150,000-400,000/ mmá¶¾.